Rhetoric and Oratory in New Spain and the Nineteenth Century in Mexico - Gerardo Ramirez Vidal (Res Rhetorica, 2024)
The conquest of America brought with it the introduction of rhetoric as a model of teaching and as a practice in the different manifestations of religious discourse, of which the preaching or sermon was the most important for scholars of the colonial era (16th-18th centuries) who, on the other hand, gave little importance to the three political genres: deliberative, epideictic and judicial or forensic, although these had not disappeared as discursive practices. The great classical deliberative oratory had taken a backseat in New Spain but continued to develop in the consistories of the mayoralties and in public debates; the judicial genre continued to be exercised in lawsuits before the Inquisition and local judicial bodies and the epideictic genre was manifested in the lives of saints and praises of various kinds. This situation changed during the 19th century, particularly in the second half, when great parliamentary oratory, civic and patriotic speeches that flooded the republic and judicial oratory flourished because of the new political conditions brought about by the struggle for independence and the triumph of liberalism, in addition to other important genres such as history and journalism. The purpose of this essay is, first, to offer an outline of oratory practices and rhetorical teaching during the Colony, emphasizing the importance of sermons and the oblivion of other discursive expressions and, second, to show the emergence of political genres during the 19th century, which reached their greatest splendor in discursive practices and liberal education.